Role of ILC2 in Viral-Induced Lung Pathogenesis - Fonseca, Wendy; Lukacs, Nicholas W.; Elesela, Srikanth; Malinczak, Carrie-Anne (Frontiers in Immunology, 2021)
Innate lymphoid type-2 cells (ILC2) are a population of innate cells of lymphoid origin that are known to drive strong Type 2 immunity. ILC2 play a key role in lung homeostasis, repair/remodeling of lung structures following injury, and initiation of inflammation as well as more complex roles during the immune response, including the transition from innate to adaptive immunity. Remarkably, dysregulation of this single population has been linked with chronic lung pathologies, including asthma, chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrotic diseases (IPF). Furthermore, ILC2 have been shown to increase following early-life respiratory viral infections, such as respiratory syncytial virus (RSV) and rhinovirus (RV), that may lead to long-term alterations of the lung environment. The detrimental roles of increased ILC2 following these infections may include pathogenic chronic inflammation and/or alterations of the structural, repair, and even developmental processes of the lung. Respiratory viral infections in older adults and patients with established chronic pulmonary diseases often lead to exacerbated responses, likely due to previous exposures that leave the lung in a dysregulated functional and structural state. This review will focus on the role of ILC2 during respiratory viral exposures and their effects on the induction and regulation of lung pathogenesis. We aim to provide insight into ILC2-driven mechanisms that may enhance lung-associated diseases throughout life. Understanding these mechanisms will help identify better treatment options to limit not only viral infection severity but also protect against the development and/or exacerbation of other lung pathologies linked to severe respiratory viral infections.